Fractional Order PID Controlled PV Buck Boost Converter with Coupled Inductor - Vanitha D; M. Rathinakumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Buck-boost converter is a good interface between PV and the load. This paper deals with comparison between PI and FOPID controlled PV fed Buck Boost Converter with Coupled Inductor (PVBBCCI) systems. Open loop PVBBCCI system, closed loop PI controlled PVBBCCI and FOPID based PVBBCCI systems are designed, modeled and simulated using Simulink and their results are presented. The investigations indicate the superior performance of FOPID controlled PVBBCCI system. The proposed system has advantages like reduced hardware count enhanced dynamic response and improved stability.